Resposta olfativa do polinizador apis mellifera a genótipos de meloeiro (cucumis melo) não atrativos à mosca-minadora (liriomyza sativae) - Farias, Lucas de Lima (2023)
The Africanized honeybee (Apis mellifera) is the main pollinator of melon (Cucumis melo L.) in Brazil, an agricultural crop of great importance for the country. However, the attractiveness of these bees to melon flowers differs depending on the volatile organic compounds (VOCs) emitted by the plants. The selection of genotypes that emit repellent VOCs that attribute resistance to pests has been suggested as an alternative to the use of pesticides but can also affect crop pollination by repelling pollinating bees. Therefore, this work aimed to investigate and select melon genotypes identified as resistant to the leaf miner fly (Liriomyza sativae spp.), but not to their pollinator. The study was carried out by identifying the volatile organic compounds present in the male and hermaphrodite flowers of the melon genotypes CNPH 06-1047-343, CNPH 11–1071-43 and CNPH 06-1047-341, with characteristics of resistance to the pest, based on the non-repellent commercial hybrids Goldex and Imperial 45. In addition, the olfactory response of A. mellifera to the volatile constituents of the studied melons was evaluated using a “Y” olfactometer. Eight volatile compounds were identified in melon flowers, four of which are common to both flower genera. In both flower genera, α-Pinene and Limonene were the most frequent compounds, but there was only a significant difference (p<0.05) between the genotypes in relation to the intensity of these dominant compounds in male flowers. The genotype CNPH 06-1047-341 stood out for being different from all other melons, presenting the highest intensity of Limonene, in addition to having one of the highest intensities of α-Pinene, in this case not differing from Goldex or CNPH 06-1047-343. There was no significant difference (p>0.05) in the frequency of entry of A. mellifera into the olfactometer arms between hybrids and melon genotypes and the control, or between hybrids and melon genotypes. In the permanence time experiments, the bees were more attracted by the control than by the volatiles of the melons, and among the melons, the genotypes did not differ from the hybrid Goldex or the hybrid Imperial 45, except for CNPH 06-1047-341, which was less attractive than Imperial 45. The results suggest that due to the intense presence of α-Pinene and Limonene in a possible high concentration, as well as the absence of a greater variety of attractive compounds in its volatile composition, the genotype CNPH 06-1047-341, in addition to repelling L. sativae spp., is not attractive to the pollinator. Nevertheless, the CNPH 06-1047-343 and CNPH 11–1071-43 genotypes, as they do not differ from commercial hybrids in terms of attractiveness to A. mellifera, are materials that can be used because despite repelling the pest, they are apparently still attractive to the pollinator. These results should be considered in genetic improvement programs and production of commercial varieties.